Dance of Awareness™: evolving a 'free-form' approach to exploring early developmental patterns in a group setting. Issue 2 (2nd July 2016) - Osbond, Clare; Brown, Tim
Abstract: This paper describes the development of the Dance of Awareness™ movement practice, including the evolution of a new variation known as Free/Form. We aim to demonstrate how this provides a meeting point for body psychotherapy and dance movement psychotherapy. We reflect on evidence gathered over many hours of practice, which we hope may be of benefit to practitioners from both disciplines and encourage joint working.